Description of the two new Microserica species from Laos and Thailand (Coleoptera: Scarabaeidae: Melolonthinae: Sericini) - Ahrens, Dirk (Zootaxa, 2005)
Two new species of Microserica Brenske are described from the Indochinese region, Microserica panzona (Laos) and M. soppongensis (Thailand). The male genitalia are illustrated and diagnostic characters from related taxa are discussed.